Pengaruh Perawatan Paliatif terhadap Kualitas Hidup Pasien Kanker Payudara - Ariyanti, Kadek Yemi; Afiyanti, Yati; Maria, Riri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the effect of palliative care on the quality of life of breast cancer patients. The research method used was a systematic review using the Research gate, Google Scholar, and PubMed databases with inclusion criteria covering 10 journals using the keywords palliative care, quality of life, and breast cancer. The research results showed that of the 10 articles reviewed, all articles showed that good palliative care would improve the quality of life in patients with breast cancer. In conclusion, there is a relationship between palliative care and the quality of life of patients with breast cancer, thus proving that palliative care has an influence on quality of life. Comprehensive palliative care for various aspects of the patient's life plays a very important role in achieving maximum quality of life in breast cancer patients. Keywords: Breast Cancer, Palliative Care, Quality of Life.